Reliability and validity of the Turkish version of the Abeer Children Dental Anxiety Scale (ACDAS) - Aylin Aslan; Tamer Tüzüner; Özgül Baygın; Nagehan Yılmaz; Serpil Sagdıc (Arbu Academic Publishing, 2021)
Aim: This study aimed to assess the validity and reliability of the Turkish version of the Abeer Children Dental Anxiety Scale (ACDAS) as a tool used for the identification and treatment of anxious children. Methods: The study sample included 122 children aged ≥7 years, and the intervention consisted of implementation of the ACDAS and the Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) by the lead researcher during the first dental visit for each child. ACDAS application was also repeated by another pediatric dentist in a smaller sub-sample of 20 children during the same visit. The lead researcher repeated the process, (i.e. application of ACDAS) in the whole study sample after two weeks. Results: The mean age of the participants was 9.84 ± 1.696 years (range: 7-12 years), and anxiety (ACDAS ≥ 26) was detected in 36.1% of the children. The Turkish version of the ACDAS exhibited high correlation with the CFSS-DS (r = 0.760; p < 0.001), and the Cronbach Alpha value (α = 0.934) showed good internal consistency. No statistically significant differences were observed in the dentist's responses to questions in the Dental and Cognitive sections when comparing the first and second applications of the scale (p > 0.05), although significant differences were observed in the Child Evaluation section (p < 0.01). The Area Under the Curve (AUC), obtained by Receiver Operative Characteristic Curve (ROC) Analysis was 0.849 indicating good diagnostic performance. Conclusions: Based on these findings, the Turkish version of the ACDAS can be considered as a valid and reliable dental anxiety scale for the identification of children concerned about dental procedures.